2017
DOI: 10.1155/2017/3212056
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Pancreatic Metastasis from Squamous Cell Carcinoma of the Lung Diagnosed by EUS-Guided Fine Needle Biopsy

Abstract: We report a case of a 70-year-old man who presented with abdominal pain and weight loss, with initial imaging showing simultaneous mass lesions in the pancreas and lungs along with extensive lymphadenopathy in the thorax up to the left supraclavicular region. Core biopsies of the left supraclavicular lymph node showed squamous cell carcinoma, which required differentiation between secondary and primary pancreatic neoplasms. Endoscopic ultrasound-guided sampling using a novel fine needle biopsy system was key t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
(10 reference statements)
0
7
1
Order By: Relevance
“…Cytomorphology alone is insufficient to distinguish between primary pancreatic cancer and metastatic cancer, but multiple immunohistochemical stain such as thyroid transcription factor on tissue specimen allows for this distinction, hence FNB is usually preferred. 10,11 However, in our case, there were no enlarged lymph nodes observed around the pancreas nor vascular invasion other than splenic vein invasion. Hence, only FNA was performed, but sufficient core tissue was not obtained.…”
contrasting
confidence: 58%
See 1 more Smart Citation
“…Cytomorphology alone is insufficient to distinguish between primary pancreatic cancer and metastatic cancer, but multiple immunohistochemical stain such as thyroid transcription factor on tissue specimen allows for this distinction, hence FNB is usually preferred. 10,11 However, in our case, there were no enlarged lymph nodes observed around the pancreas nor vascular invasion other than splenic vein invasion. Hence, only FNA was performed, but sufficient core tissue was not obtained.…”
contrasting
confidence: 58%
“…2,7 In a recent study of single institution in Korea, 58% of patients with metastasis to pancreas were found at follow-up imaging without any symptoms, and 42% were found with related symptoms. 6 On EUS evaluation, pancreas metastatic lesion is known to show relatively well-define borders compared to primary pancreatic cancer, 10 but there have been studies that state that it is difficult to distinguish between metastatic lesion and primary pancreatic cancer. Therefore, pathological confirmation is the recommended diagnostic tool in this case.…”
mentioning
confidence: 99%
“…EUS-guided FNA/biopsy is an established and widely used tissue sampling technique for the pancreas[8], and there is no doubt that this technique will provide promising results in the diagnosis of pancreatic diseases. However, the amount of specimens that can be obtained with a conventional FNA needle is limited and can preclude diagnoses that require detailed histological assessment, such as AIP [9] or neoplasms with atypical histology [10]. In this study, we have shown that the Franseen needle obtained significantly larger samples than were obtained with a conventional FNA needle, even from the pancreatic head or uncinate process, which have been difficult to sample with existing core needles [1115].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, imaging studies can only precisely evaluate the stage of disease, whereas histopathological examination can more accurately distinguish primary from metastatic pancreatic lesions (12). Percutaneous fine-needle biopsy of the pancreatic tumor, guided by either CT or EUS, can help establish a solid diagnosis (13,14). Following meticulous evaluation of preoperative imaging studies and assessment of the patient's clinical condition, surgical teams can determine whether the patient is eligible to undergo resection with curative intent (10).…”
Section: Discussionmentioning
confidence: 99%
“…According to their results, the mean postoperative survival following pancreatic resection (8 patients; 61.5%) was 28.9 months (range, 1-91 months) compared with 2 months (range, 5-30 months) for patients who were administered palliative chemotherapy and/or radiation (5 patients; 38.5%) (10). However, in the case of metastatic lesions from primary squamous cell lung carcinoma, the evidence is poor and surgical treatment is rarely attempted due to extensive or unresectable pancreatic disease (6,7,10,14).…”
Section: Discussionmentioning
confidence: 99%